Soroprevalência de doenças infecciosas em doadores de sangue do hemocentro regional de Cruz Alta-Rio Grande do Sul - Martins, Ana Paula Becker; Silva, Brenda da; Molin, Diovana Brondani Dal; Mendes, Graziella Alebrant (Clinical and Biomedical Research, 2015)
Introduction: Clinical and serological screening of blood donors is an essential strategy to prevent transmission of infectious agents during blood transfusion. Objective: To determine the seroprevalence of infectious diseases in blood donors at the Blood Center of Cruz Alta. Method: Prospective cross-sectional study conducted at the Blood Center of Cruz Alta, Rio Grande do Sul, from January 2013 to June 2014. Results: 6139 donations were made during the study period, 280 (4,56%) of which were considered unfit for presenting some positive serological marker. The average age of unfit donors was 38 years, and 171 (61.1%) donors were male. Regarding the serological markers, 151 (46.1%) donors were positive for anti-HBc, 15 (5.4%) for HBsAg, 21 (7.5%) for anti-HCV, 15 (5.4%) for HIV, 19 (6.8%) for HIV-Ag AC, 6 (2.1%) for HTLV-I /II, 64 (22.9%) for Chagas disease, and 37 (13.2%) for syphilis (VDRL). Conclusion: The results show the importance of serological screening in order to ensure transfusion safety and prevent infection of individuals who need blood transfusions.